Application of the RSM-CCD Method in Making Mozzarella Cheese Using Pineapple Juice and Coagulation Time - Riztyani, Khofifah; Hermanuadi, Didiek (International Journal of Technology, Food and Agriculture, 2024)
Mozzarella cheese is a type of fresh cheese which is characterized by being elastic, fibrous and soft. This research was carried out using the RSM-CCD (Response Surface Methodology Central Composite Design) method which aims to determine the optimum conditions for coagulation time and pineapple juice concentration in making mozzarella cheese with a combination of 13 treatments obtained from the expert-13 design software. The research method uses two factors, namely coagulation time with a coagulation time limit of 25-35 minutes and pineapple juice concentration with a limit of 2.5-3.5%. The responses used are curd weight , water content, and elongation using a quadratic model. The research results showed that the optimal treatment combination was a coagulation time of 25 minutes with a pineapple juice concentration of 2.5%, the resulting desirability value was 57.4%. From the solution results, an estimate of the maximum response was obtained with an average value of curd weight of 248 grams, water content of 41.55%, and elongation of 17.95 inches. The confirmation results obtained an average of curd weight data of 244.5 grams, water content of 38.97%, and elongation of 17 inches. The average confirmation test data for each response showed that the results were in accordance with the predicted value with a confidence interval ratio of 95%.